Tổng hợp và đặc trưng vật liệu aluminophotphat mao quản trung bình - Viễn, Võ; Hùng, Nguyễn Phi (Vietnam Journal of Chemistry, 2014)
Mesoporous aluminophosphates were synthesized using [(CH3)2CHO]3Al and H3PO4as sources of Al and P, respectively. The samples were characterized by X-ray diffraction, transmission electron microscopy and thermogravimetric analysis. The influence of preparation of gel and synthesis temperature on the synthesis was investigated. The results show that when mixing the sources of Al and P, low H3PO4/Al2O3ratios resulted in a decrease in hexagonal symmetry of the product, and that an increase in synthesis temperature caused phase transformation from hexagonal to lamellar structure